Drilling mud material cost saving through utilization of treated Malaysian local bentonite - Sonny Irawan, Sonny Irawan; Samsuri, Ariffin (2007)
Based on the result of Geological Survey Department Malaysia investigation, the bentonite resources in Sabah is large. In order to reduce the overall cost in oilwell drilling and completion, the development of Sabah bentonite as drilling mud material has been initiated. Two groups of samples from the Andrassy and Mansuli area in Sabah were tested. Mineralogically the samples were characterized as low grade Ca-Mg smectite. The dominant gangue mineral is ferrous ion with small amounts of kaolinite, quartz, illite, muscovite and hematite. Iron is present as magnetite and as amorphous oxides and hydroxides. Characterization of these samples indicated that the bentonite response for Na-exchange was poor while their hydration, plastic and rheological properties were inferior to those of commercial bentonite (WYBEN). The sample was processed by crushing followed by aero cyclone to give pre-concentrates which were extracted with diluted oxalic acid and activated with sodium carbonate. Application of such simple flow sheet effectively removed the majority of the associated ferrous ion. These concentrates were further refined by a series of organic acid and alkaline treatment prior to their evaluation as industrial bentonite. The mineralogy, chemical analysis and physical properties offinal concentrates and their activated products successfully match the required specifications for drilling mud industrial processes. Utilization of these bentonite, after their extracting and activation, can represent a value added to the Sabah economy by minimizing the imported bentonite used by oil and gas industry.